FRI0295 Rituximab Retention Rate in Clinical Practice: A Large Multicentre Italian Cohort of Rheumatoid Arthritis Patients. (10th June 2014) - Batticciotto, A.; Covelli, M.; Dinoia, L.; Rinaldi, A.; Giacuzzo, S.; Govoni, M.; Biasi, D.; Dal Forno, I.; Benucci, M.; Li Gobbi, F.; Caporali, R.; Todoerti, M.; et al.
Abstract : Background: Rituximab (RTX), a chimeric monoclonal antibody targeting CD20 B cell antigens, is a safe and effective treatment for rheumatoid arthritis (RA) [1]. It has been approved for RA patients who have inadequately responded to one or more anti-TNF agent and has recently been demonstrated to be significantly more effective after a first anti-TNF than switching to a second [2]. Long-term extensions of randomised controlled trials have demonstrated that prolonged RTX exposure of up to 9.5 years does not affect its safety, but there are no data concerning real-life clinical experience. Objectives: The aim of this multicentre clinical study was to evaluate the retention of RTX treatment in patients with RA. Methods: The clinical records of 472 RA patients treated with RTX from August 2006 to December 2013 in ten Italian rheumatology centres were reviewed, and treatment survival and the impact of selected variables were evaluated using Kaplan-Meier and Cox survival analyses. Results: Four hundred and seventy-two patients with a diagnosis of RA based on the 1987 ACR classification criteria (81.6% female; mean age 56.2±12.8 years; mean disease duration 10.5±8 years; 76.3% RF positive; 75% anti-CCP positive) were treated with RTX for a mean of 40.1±26.37 months (range 0-122). Seventy-six percent were co-treated with MTX, and 24% had previously received two or more anti-TNF agents. Their median DAS28 score at baseline was 5.07±1.3. For patients completing at least 12, 24, 36, 48 and 60 months of follow-up, the retention rates were respectively 87.9%, 78.8%, 72.5%, 67.6% and 63.8% (Fig. I) Treatment discontinuations because of adverse events and inefficacy had a similar temporal trend. Multivariate analysis (Cox regression) showed that none of the considered predictive variables was significantly associated with treatment survival: gender p=0.399; age p=0.486; disease duration p=0.999, baseline DAS28 p=0.412; number of previous anti-TNFα failures p=0.975; the presence of RF p=0.513; MTX treatment p=0.340. Conclusions: Our findings show that 63.8% of RA patients continued treatment with RTX for 60 months. References: Chi Chiu Mok. Rituximab for the treatment of rheumatoid arthritis: an update. Drug Des Devel Ther. 2013;8:87-100 Emery P, et al. Rituximab versus an alternative TNF inhibitor in patients with rheumatoid arthritis who failed to respond to a single previous TNF inhibitor: SWITCH-RA, a global, observational, comparative effectiveness study. Ann Rheum Dis. 2014. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3994